Acute proptosis: Unusual initial presentation of sinonasal inverted papilloma - Ibrahim, Norihan; Abdullah, Baharuddin; Kandasamy, Regunath; Othman, Nor Hayati; Ibrahim, Mohtar; Hussein, Adil (Elsevier, 2017)
Inverted papilloma is an uncommon histopathological finding of maxillary sinus tumor. We reported here a rare case of inverted papilloma of maxillary sinus presented initially with ipsilateral proptosis. A middle-aged lady with history of having allergic rhinitis presented with progressive left eye proptosis. Assessment revealed presence of orbital mass arising from paranasal sinus, in which the histopathological examination was initially inconclusive, and later it turned up to be inverted papilloma, partly with malignant transformation. High index of suspicion is necessary especially in those patients with recurrent non-specific sinonasal symptoms, which may need repeated biopsy and histopathological examination. Ocular manifestation signifies a more advance disease.